Content validity of the instrument ‘Picture My Participation’ for measuring participation of children with and without autism spectrum disorder in mainland China - Liya Li; Berit Møller Christensen; Marita Falkmer; Yue Zhao; Karina Huus (Scandinavian Journal of Occupational Therapy)
Background Picture My Participation (PMP) is a valid instrument for measuring participation of children with disabilities, but it has not yet been evaluated for its content validity for children with autism spectrum disorders (ASD) in mainland China.Aim To explore the content validity of the simplified Chinese version of PMP (PMP-C; Simplified) for children with ASD and typically developing (TD) children in mainland China.Methods A sample of children with ASD (n = 63) and TD children (n = 63) recruited through purposive sampling were interviewed using the PMP-C (Simplified), which contains 20 items of everyday activities. Children rated attendance and involvement on all activities and selected three most important activities.Results Children with ASD selected 19 of 20 activities as the most important activity while TD children selected 17 activities. Children with ASD used all scale points for rating attendance and involvement on all activities. TD children used all scale points for rating attendance and involvement in 10 and 12 of 20 activities, respectively.Conclusion The contents of 20 activities of PMP-C (Simplified) were relevant for all children and especially for children with ASD for assessing participation in community, school and home activities.